DENEYSEL NÖROPATİK AĞRI MODELİNDE NGF VE ANTİ NGF'NİN ROLÜ - TOPRAK, GONCA ÇAĞLAR (Fırat Üniveristesi, 2007)
Sinir sisteminin herhangi bir bölümünün hasarı ve / veya disfonksiyonu sonucuoluşan nöropatik ağrının mekanizmaları komplekstir. Bu karmaşık süreçte NerveGrowth Factor (NGF) de yer almaktadır. Nöropatik ağrı mekanizmalarını anlamak için,günümüze değin hayvan modellerinde ve kliniklerde pek çok araştırma yapılmış vetedavi seçenekleri geliştirilmiş olsa da halen ağrı tamamen giderilememektedir. Buçalışmada, nöropatik ağrılı hayvan modelinde NGF ve anti-Nerve Growth Factor (Anti-NGF)'nin etkilerini belirlemeyi amaçladık.Yerel etik kurul onayı ile Wistar-albino cinsi 24 adet erkek sıçan çalışmayaalındı. Denekler randomize olarak 4 gruba ayrıldı. Gruplar kontrol grubu, serumfizyolojik grubu, NGF ve anti-NGF grubu olarak adlandırıldı. Çalışmanın ilk günübütün deneklerin mekanik ve termal (sıcak, soğuk) ağrı eşikleri ölçüldü ve bazaldeğerler olarak kaydedildi. Aynı gün, kontrol grubu haricindeki tüm deneklerin solsiyatik sinirine Kronik Konstriktif Hasar (KKH) uygulandı. Süregelen zamanda, her güntüm deneklerin mekanotermal ağrı eşikleri ölçüldü. KKH uygulanan tüm deneklerdenöropatik ağrı geliştiği 21. günde saptandı. Nöropatik ağrı gelişiminden sonra, 28 günboyunca kontrol grubuna herhangi bir ilaç uygulanmadı. SF grubuna hergün SF s. c.,NGF grubuna 35 nanogram/gram NGF s. c., anti-NGF grubuna 9 nanogram/gram anti-NGF s. c. olarak uygulandı. Tüm deneklerin 28 gün boyunca mekanotermal ağrı eşikleriölçüldü.NGF'nin mekanik hiperaljeziyi 22- 32., sıcak hiperaljezisini 22-31., soğukhiperaljezisini 22-28. günler arasında arttırdığı saptandı..Anti- NGF'nin mekanik hiperaljeziyi 22-29., sıcak hiperaljezisini 22-28.,soğuk hiperaljezisini 22-27. günlerde azalttığı saptandı.Sonuç olarak sistemik uygulanan NGF nöropatik ağrıyı arttırmakta, anti-NGFise ağrıyı hafifletmektedir.Anahtar Kelimeler: NGF, anti- NGF, hiperaljezi, nöropatik ağrı

THE EFFECT OF SYSTEMIC APPLICATION OF NGF AND ANTI-NGF ONEXPERIMENTAL NEUROPATHIC PAIN MODELThe mechanisms of neuropathic pain due to damage and/or dysfunction of thepart of nervous system are complicated. Nerve growth factor (NGF) is present in thesecomplex processes. Although there have been numerous experimental and clinicalinvestigations for understanding of the pathophysiology and lots of treatment modalitieshave been implicated for neuropathic pain management so far, pain could not beobviated yet. In this study, the effect of NGF and Anti-Nerve Growth Factor (anti-NGF)in experimental neuropathic pain model was aimed.Upon an approval of Local Ethic Committee obtained, 24 male Wistar-albinorats were taken into study and divided into 4 groups. All groups referred as controlgroup, saline group, NGF group, and anti-NGF group. Mechanical and thermal (heat,cold) pain thresholds were measured and recorded for each animal in the first day of theexperiment. In the same day, chronic constriction injury (CCI) was introduced to leftsciatic nerve for each animal except control groups. In the following days, mechano-thermal pain thresholds were measured for every day for each animal. It has been notedthat neuropathic pain was existed in 21st day of experiment in all CCI applied rats.Following neuropathic pain was obtained nothing was administered to control groupduring 28 days. For saline group; saline was administered s.c. whereas for NGF group, adose of 35 nanogram/gram NGF was administered s.c., for anti-NGF group, a dose of 9nanogram/gram anti-NGF was administered s.c. Mechano-thermal pain thresholds weremeasured for each animal during followed 28 days.It was determined that NGF increased mechanical hyperalgesia, heathyperalgesia, cold hyperalgesia between 22-32 days, 22-31 days, 22-28 days,respectively. However, it was noted that anti-NGF reduced mechanical hyperalgesia,heat hyperalgesia, cold hyperalgesia between 22-29 days, 22-28 days, 22-27 days,respectively.In conclusion; systemic applied NGF increased neuropathic pain, whereas anti-NGF diminished of this kind of pain.Key Words: NGF, anti-NGF, hyperalgesia, neuropathic pain.
The effect of systemic application of NGF and anti NGF on experimential neuropathic pain model
Keywords: Anestezi ve Reanimasyon